SOME STUDIED RESULTS ON THE RESIDUAL CURRENT IN THE SOUTH-CENTRAL COASTAL WATERS OF VIET NAM - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2009)
Studied results show that tidal residual current in the south-central waters has no significant influence, its maximum velocity is below 4cm/s. However, when studying the influence of the resultant current of 5 tidal constituents M 2 , S 2 , N 2 , O 1 , K 1 , the residual current velocity can reach 22cm/s in the coastal waters from Binh Thuan to Tra Vinh, but it is much weaker in other coastal areas.Using  the  same  finite  element  method,  the  calculation  results  obtained  by  the  2D nonlinear (influence of thermo-haline distribution not included) and 3D nonlinear (influence of thermo-haline  distribution  included)  problems  are  different  in  direction  of  the  maximum velocity and in the occurrence/no occurrence of a cyclone eddy in the south of Binh Thuan waters. This is a complicated and new problem in the study area, which we will try to clarify in the next study.